Therapeutic outcomes, immunological responses to treatment and vaccine preventative strategies for Hepatitis C in HIV seropositive individuals - Bannan, Ciaran (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2018)
Introduction: HIV and Hepatitis C virus (HCV) represent significant causes of morbidity and mortality worldwide. Because of shared routes of transmission co-infection is common. Recent advances in treatment for both HIV and HCV look set to significantly alter the natural history of both diseases and offer long-term hope for patients. The advent of direct-acting antiviral (DAA) therapy for HCV has markedly improved therapeutic outcomes for patients engaged in care. Despite, excellent tolerability and high rates of sustained virological response (SVR) with these new agents, they are costly, associated with drug-drug interactions, do not prevent against re-infection and are not 100% effective. Additionally, HCV viral resistance may represent a challenge in the future. This DAA therapy will have a limited impact on the burden of HCV-related disease on a population level unless barriers to HCV education, screening, evaluation and treatment are addressed and treatment uptake improves. At present, no commercial vaccine exists for prevention of HCV. Aims/Methods: The aims of this thesis were threefold. Firstly, I looked to examine therapeutic outcomes for patients with HIV/HCV co-infection treated for HCV from 2001 to 2016. Secondly, further understanding of the complex interaction between HCV and the immune system is likely to yield benefits in terms of therapeutic and preventative strategies. We looked to examine alterations in the IFN-alpha JAK-STAT signaling pathway in primary immune cells of co-infected patients as a result of HCV treatment with a Telaprevir-based regimen. Finally, towards a preventative strategy for HCV in HIV patients, we looked to examine the safety and immunogenicity of novel vaccine candidates (AdCh3NSmut1 and MVA-NSmut) delivered in a prime-boost regimen. Results: Regarding therapeutic outcomes, a significant difference in mortality and liver-related morbidity was observed between patients who obtained and did not obtain a SVR with interferon-based treatment regimens. Outcomes for people who inject drugs (PWIDs) were similar to non-PWIDs. An increase in treatment uptake and SVR rates was seen with the new DAA regimens. We found that STAT1 protein levels are reduced from primary immune cells in patients with HIV/HCV co-infection and Telaprevir-based regimens resulted in on-treatment restoration of STAT1 levels in these patients. Finally, we showed that AdCh3/MVA vaccination in HIV-infected patients is safe and induced T-cell responses in the majority of antigenic pools tested by ELISpot assay in all individuals. Discussion: This work has chronicled the improvements in therapeutic outcomes for HCV therapy in co-infected patients and shown the benefits of obtaining a SVR in HIV/HCV co-infected patients. We have outlined a previously undescribed phenomenon in HIV/HCV co-infected patients where DAA therapy has resulted in a significant increase in STAT1 protein from primary immune cells. This work has also evaluated the safety and immunogenicity of a novel vaccine strategy in HIV-positive patients. The vaccine strategy has been shown to be safe and highly immunogenic. Data from an on-going Phase 2 study looking at efficacy of this vaccine regimen are eagerly awaited.
APPROVED
Keywords: Hepatitis C; HIV; JAK-STAT; Vaccine; STAT1; IFN-alpha; Direct-Acting Antiviral; ELISpot